1997
DOI: 10.1063/1.869434
|View full text |Cite
|
Sign up to set email alerts
|

Molten droplet deposition and solidification at low Weber numbers

Abstract: Low Weber number deposition of small molten droplets on cold targets is of importance in certain dropwise buildup processes, but at this time, critical elements are absent from our theoretical understanding of the deposition process, and prediction from basic principles is not possible. This paper lays down a framework for understanding low Weber number deposition in terms of similarity laws and experimentation. Based on experiments from the highly viscous limit to the inertia-dominated limit, correlations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
262
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 361 publications
(279 citation statements)
references
References 17 publications
12
262
0
5
Order By: Relevance
“…It is interesting to note that for values of λ Re * < 0.1, no oscillatory motion was seen in the work by Ding and Spelt [19]. In Schiaffino and Sorin [18] it is experimentally determined that the transition between under-damped oscillations to over-damped decay (no oscillations) occurs as Oh increases above 1 × 10…”
Section: Dimensionless Equations and Timescalesmentioning
confidence: 98%
See 2 more Smart Citations
“…It is interesting to note that for values of λ Re * < 0.1, no oscillatory motion was seen in the work by Ding and Spelt [19]. In Schiaffino and Sorin [18] it is experimentally determined that the transition between under-damped oscillations to over-damped decay (no oscillations) occurs as Oh increases above 1 × 10…”
Section: Dimensionless Equations and Timescalesmentioning
confidence: 98%
“…Characteristic inertial effects, such as triple-line position oscillations and large droplet curvature variations, are reduced for Oh > 0.01 and eliminated for Oh > 1 [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1); hence, the fraction that solidifies during impact may have a much stronger influence on droplet spreading. This condition has been considered by Schiaffino and Sonin, 18 who produced dimensionless analytical expressions to calculate the ratio between droplet spreading and solidification time. They found that, although the solidification time of a droplet 25-100 m in size was several orders of magnitude greater than the time taken to reach maximum spreading diameter, this diameter was controlled by solidification of the contact line.…”
mentioning
confidence: 99%
“…The final shape and surface texture of the resultant printed structure was dependent on conditions that include the wettability of the substrate and its temperature, print head temperature, gap distance from the print head to the substrate and droplet material [34][35][36] . The scalloping behaviour was due to the droplets being cooled quicker than optimal during jetted flight, after landing on the substrate, merging with the previous deposited droplet and partially retained their individual rounded contact lines [37] . Printing wax allowed the creation of a range of different complexities and channel widths that allowed the creation of thick impermeable blocks, to channels as small as 30 µm.…”
Section: Inkjet Printing Of Wax Guidesmentioning
confidence: 99%